2018
DOI: 10.2478/foecol-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Carabid communities (Coleoptera, Carabidae) in differently managed forage legume stands in the Podpoľanie region (Central Slovakia)

Abstract: The paper presents the results of studies on the communities of Carabids from the land registry area of the Očová village (Podpoľanie region, Central Slovakia). The research was carried out in two consecutive vegetation periods on two different agricultural plots with alfalfa (Medicago sativa L.): the first of them (locality Nadhájniková) was managed intensively, and the second one (locality Koteľnice) was characterized by a nature-friendly, low-input agro-environmental management form, without application of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…Several studies confirmed our findings (Naidenko and Grechkanev, 2002;Weller and Ganzhorn, 2003;Timofeeva and Savosin, 2009;Gordienko and Sukhodolskaya, 2011;Kalivoda et al, 2011;Sukhodolskaya, 2011;2013, 2014, 2016Vician et al, 2018).…”
Section: Resultssupporting
confidence: 85%
“…Several studies confirmed our findings (Naidenko and Grechkanev, 2002;Weller and Ganzhorn, 2003;Timofeeva and Savosin, 2009;Gordienko and Sukhodolskaya, 2011;Kalivoda et al, 2011;Sukhodolskaya, 2011;2013, 2014, 2016Vician et al, 2018).…”
Section: Resultssupporting
confidence: 85%
“…The data obtained by us did not confirm the differences in the dominance of species in ecological and conventional agriculture, which could be caused by the surrounding agricultural areas with conventional agricultural management and the termination of the ECO research area in 2018. Vician et al (2010) identified eudominant species of P. melanarius and P. rufipes on different management of agricultural areas, without observing significant differences in dominance. By evaluating the frequency of occurrence of individual species, we conclude that the P. melanarius and P. rufipes species were constant during the three-year monitored period.…”
Section: Species Similaritymentioning
confidence: 91%
“…Morphological variability within populations is a reflection of the plasticity of the development of a species, and in different populations is a measure of adaptive plasticity of a species (Kawano, 2006(Kawano, , 2016. There are articles devoted to the influence of the type of food objects (Bonal et al, 2011;Martynov and Brygadyrenko, 2018;Martinková et al, 2019), the temperature and nature of the substrate (Ernsting and Isaaks, 1997), competition (Okuzaki and Sota, 2018), biogeography (influence of altitude, climate) and anthropogenic factors (Vician et al, 2018;Sowa and Skalski, 2019) on the morphological variability of beetles. Little research has been devoted to the influence of environmental factors on the morphological variability of ground beetles (Coleoptera, Carabidae).…”
Section: Introductionmentioning
confidence: 99%